Litigância climática e ativismo societário: a crescente onda de litígios climáticos e os desafios a serem enfrentados na responsabilização de corporações por danos ao meio ambiente - Guarita, Marcelo Barretto (2025)
This paper examines the evolution of climate litigation, focusing on the accountability of corporations and their directors for conduct or omissions incompatible with environmental obligations. Through an analysis of landmark international cases—Urgenda v. Netherlands, Milieudefensie v. Shell, and ClientEarth v. Shell Board—the research highlights the shift in climate litigation from state-centered actions to corporate and individual liability. In the Brazilian context, the study explores the still incipient development of corporate climate litigation, identifying legal and institutional barriers as well as potential enforcement mechanisms, including arbitration. The study concludes that climate litigation, when articulated with ESG governance and fiduciary duties, constitutes a new frontier in legal accountability for the climate crisis